The physical and psychosocial functionalities of female circumcision practice among meranaos in the Philippines - Manalocon-Basher, Salmah Lao. (2015)
This study investigated the underlying beliefs and practices of female circumcision among Meranaos in the Philippines. This also determined the common procedure followed in performing the said practice.
Nursing.
Keywords: Abstract; Ethnology; Female circumcision -- Philippines; Meranaos